A Comprehensive Analysis for Expression, Diagnosis, and Prognosis of m5C Regulator in Breast Cancer and Its ncRNA–mRNA Regulatory Mechanism - Liu, Jingxing; Xiao, Shuyuan; Chen, Jing; Lou, Weiyang; Chen, Xu (Frontiers in Genetics, 2022)
Recent studies have well demonstrated that 5-methylcytosine (m5C) regulators play pivotal roles in pathological conditions, including cancer. This study firstly tried to identify potential 5-methylcytosine (m5C) regulators in breast cancer by combination of expression, diagnosis and survival analyses, and then established a ncRNA-mRNA network accounting for m5C regulators’ roles in breast cancer. Among 13 m5C regulators, DNMT3B and ALYREF were significantly upregulated in breast cancer and their high expression indicated unfavorable prognosis. Both DNMT3B and ALYREF possessed the statistical abilities to distinguish breast cancer from normal breast samples. Moreover, five potential upstream miRNAs (let-7b-5p, miR-195-5p, miR-29a-3p, miR-26a-5p and miR-26b-5p) of m5C regulators could not only serve as independent prognostic predictors but also together made up a promising miRNA prognostic signature in breast cancer. Next, upstream potential lncRNAs of the five miRNAs were predicted and analyzed. Pathway enrichment analysis revealed that the target genes of these miRNAs were markedly enriched in some cancer-related pathways, and further investigation indicated VEGFA and EZH2 were found to be the most potential target genes in m5C regulators-related ncRNA-mRNA network in breast cancer. These findings comprehensively provided key clues for developing m5C regulators-related effective therapeutic targets and promising diagnostic biomarkers in breast cancer.